Management of Respiratory Failure in Cancer Patients: A Narrative Review - salsa Syifa; Cecep Eli Kosasih (Padjadjaran Acute Care Nursing Journal, 2022)
Introduction: According to WHO, in 2018 18.1 million people worldwide had cancer, and 9.6 million people died. Acute organ failure is often found in cancer patients, especially respiratory failure where this is related to co-morbidities, cancer treatment, or the malignancy itself. Purpose: To identify management that can be done in cancer patients who experience respiratory failure. Methods: This literature review used a narrative review design using the PubMed, Sciencedirect, and Proquest databases. The criteria for the articles used were full-text, English-language articles, the year the research was published was between 2012-2022, the research design was a randomized control trial, quasi-experimental, qualitative study, retrospective study, and the research to be analyzed discussed the management of respiratory failure in patients with cancer. The articles obtained were extracted according to the criteria and then grouped and reviewed. Results: There are 6 articles that meet the requirements and contain various types of management of respiratory failure in cancer patients and are grouped into nursing interventions, ventilator installation, oxygenation support, administration of pharmacological medication. Conclusion: Various kinds of management in dealing with respiratory failure in cancer patients can be applied to provide benefits to patients. It is hoped that there will be further research regarding the effectiveness of the management of respiratory failure in cancer patients so that it can help patients to improve their condition and prevent death.